Long-term Outcome of Punctal Cauterization in the Management of Ocular Surface Diseases - Wang, Yvonne (Cornea, 2021)
PURPOSE: To evaluate long-term outcome of surgical occlusion of lacrimal puncta using thermal cautery in the management of ocular surface diseases. METHODS: We reviewed medical records of 80 consecutive patients from a single academic center who underwent punctal cauterization. Patient demographics, ocular history, symptoms and signs of ocular surface diseases pre- and post-cauterization were recorded. RESULTS: A total of 80 patients (171 puncta) were included with an average age of 59 years and follow-up duration of 27 months. The most common ocular morbidity was ocular graft-versus-host disease (n=36), followed by primary keratoconjunctivitis sicca (n=15). Indications for punctal cauterization included plug loss (n=51), difficulty in plug fitting (n=11), plug related complications (n=6), recanalization of prior cauterization (n=7), and severe ocular surface disease requiring permanent punctal closure (n=4). After punctal cauterization, the percentage of eyes with severe (21%) and moderate (25%) dry eye decreased significantly (8% and 19% at three months and 6% and 17% at twelve months, p=0.0006). Fifty-four percent of patients reported improvement in their symptoms. The rate of recanalization was 21% during the follow-up period. The use of topical corticosteroids was associated with higher recanalization rate. Associated complications were limited to temporary pain and swelling. CONCLUSIONS: Punctal cauterization is an effective modality in treating severe ocular surface diseases in patients who repeatedly lose punctal plugs and can be easily performed in a clinic setting without major complications. However, cauterization may need to be repeated in up to a quarter of cases due to recanalization.